Characteristics of paradoxical tuberculosis-associated immune reconstitution inflammatory syndrome and its influence on tuberculosis treatment outcomes in persons living with HIV. (September 2020) - Narendran, Gopalan; Jyotheeswaran, Keerthana; Senguttuvan, Thirumaran; Vinhaes, Caian L.; Santhanakrishnan, Ramesh K.; Manoharan, Tamizhselvan; Selvaraj, Anbhalagan; Chandrasekaran, Padmapriyadarsini; Menon, Pradeep A.; Bhavani, Kannabiran P.; Reddy, Devarajulu; Narayanan, Ravichandran; et al.
Abstract: Objective: The influence of tuberculosis (TB)-immune reconstitution inflammatory syndrome (IRIS) on TB treatment outcomes and its risk factors were investigated among people with human immunodeficiency virus (HIV) and co-infected with TB. Methods: Newly diagnosed, culture-confirmed, pulmonary TB patients with HIV and enrolled in a clinical trial (NCT00933790) were retrospectively analysed for IRIS occurrence. Risk factors and TB outcomes (up to 18 months after initiation of anti-TB treatment [ATT]) were compared between people who experienced IRIS (IRIS group) and those who did not (non-IRIS group). Results: TB-IRIS occurred in 82 of 292 (28%) participants. Significant baseline risk factors predisposing to TB-IRIS occurrence in univariate analysis were: lower CD4 + T-cell count, CD4/CD8 ratio, haemoglobin levels, presence of extra-pulmonary TB focus, and higher HIV viral load; the last two retained significance in the multivariate analysis. After 2 months of ATT commencement, sputum smear conversion was documented in 45 of 80 (56.2%) vs. 124 of 194 (63.9%) ( p  = 0.23), culture conversion was in 75 of 80 (93.7%) vs. 178 of 194 (91.7%) ( p  = 0.57) and the median decline in viral load (log10 copies/mm 3 ) was 2.7 in the IRIS vs. 1.1 in the non-IRIS groups ( p  < 0.0001), respectively. An unfavourable response to TB therapy was detected in 17 of 82 (20.7%) and 28 of 210 (13.3%) in the IRIS and non-IRIS groups, respectively ( p  = 0.14). Conclusions: TB-IRIS frequently occurred in people with advanced HIV infection and in those who presented with extra-pulmonary TB lesions, without influencing subsequent TB treatment outcomes.